AN ANALYSIS OF THE USE OF GRAMMATICAL AND LEXICAL COHESION IN THESES WRITTEN BY UNDERGRADUATE STUDENTS MAJORING IN ENGLISH OF ISLAMIC UNIVERSITY OF RIAU - Putra, Almalikul Ikhwanda (Linguists : Journal of Linguistics and Language Teaching, 2018)
The purposes of this research were to find out (a) the occurrence and the percentages of the use of grammatical and lexical cohesion in theses written by undergraduate students majoring in English of Islamic University of Riau, (b) the errors found in the use of grammatical and lexical cohesion, (c) why students made errors in the use of grammatical and lexical cohesion. A content analysis design was used in this research. Content analysis is commonly used to analyze texts including interview transcripts, diaries, or document. The samples were 25 theses of undergraduate students majoring in English of Islamic University of Riau written between 2012 and 2016. The data were based on (1) document, in terms of first and fourth chapter of 20 theses written by undergraduate students majoring in English of Islamic University of Riau, (2) questionnaire to find out the causes of the errors in the use of grammatical and lexical cohesion. The results showed that (a) the highest occurrence and percentage of the use of grammatical and lexical cohesion was 47.50% on conjunction and the lowest was 0.07% on substitution, (b) The errors that students made in the use of grammatical and lexical cohesion are mostly in terms of collocation and repetition, (c) The reasons why students made errors in the use of cohesive devices in writing their theses were (1) the students still lack of grammar knowledge, and (2) the students also paid less attention to the use of cohesive devices in writing their theses.